2017
DOI: 10.1093/ofid/ofx163.1209
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, and Excretion of 14C-APX001 after Single-Dose Administration to Rats and Monkeys

Abstract: BackgroundAPX001 is a small-molecule therapeutic agent in clinical development for the treatment of invasive fungal infections (IFI).MethodsThe absorption, distribution and excretion profiles of [14C]APX001-derived radioactivity were determined in rats (albino and pigmented) and monkeys. Rats (some implanted with bile duct cannulae) were administered a single 100 mg/kg oral dose or a 30 mg/kg intravenous (IV) dose. Monkeys were administered a single 6 mg/kg IV dose. Samples of blood, urine, feces and bile, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…In the current model of disseminated C. auris infection, APX001 resulted in significantly better survival than anidulafungin. Both APX001 and anidulafungin demonstrated significant and equivalent decreases in kidney and lung CFU at 48 h. However, only APX001 demonstrated a reduction in brain CFU, a finding consistent with the brain penetration observed in 14 C-APX001 distribution studies where radioactivity was detected in tissues associated with invasive fungal infections ( 33 ). This contrasts with the poor CNS penetration observed for the echinocandins ( 30 ).…”
Section: Discussionsupporting
confidence: 76%
“…In the current model of disseminated C. auris infection, APX001 resulted in significantly better survival than anidulafungin. Both APX001 and anidulafungin demonstrated significant and equivalent decreases in kidney and lung CFU at 48 h. However, only APX001 demonstrated a reduction in brain CFU, a finding consistent with the brain penetration observed in 14 C-APX001 distribution studies where radioactivity was detected in tissues associated with invasive fungal infections ( 33 ). This contrasts with the poor CNS penetration observed for the echinocandins ( 30 ).…”
Section: Discussionsupporting
confidence: 76%
“…APX001 has been shown to be effective in mouse models of Candida albicans (18, 22, 32), Candida auris (33), and Cryptococcus neoformans (17) infections, as well as Aspergillus and Fusarium infections (16). In addition to increased survival, a reduction in the colony counts of fungi in the lungs, kidneys, and brain tissues of infected mice has been observed, consistent with 14 C-APX001 studies that demonstrated wide tissue distribution in rats and monkeys, especially in tissues associated with invasive fungal infections (34). Notably, treatment with APX001 lead to a significant reduction in brain CFU in both a rabbit model of hematogenous C.…”
Section: Discussionsupporting
confidence: 82%
“…The absorption, distribution and excretion profiles of [ 14 C]FMGX-derived radioactivity were explored in rats using a single dose of 100 mg/kg PO or 30 mg/kg IV, whereas monkeys were administered a single 6 mg/kg IV dose [ 67 ]. Samples were analyzed for total radioactivity content by liquid scintillation counting, and carcasses were analyzed by quantitative whole-body autoradiography (QWBA).…”
Section: Tissue Distributionmentioning
confidence: 99%